Water Logging Menace in Metro Cities Need a Conceptual Change in Approach for its Permanent Solution - Prasad, Mahesh (AMC Indian Journal of Civil Engineering, 2021)
Cities in India have witnessed a colossal growth in area as well as population in last few decades. As a result, the civic facilities in cities have come under great stress. The drainage of storm water, water supply system, roads, electric supply system, waste disposal systems generally need a major augmentation. Storm water drainage due to encroachment of water bodies, abnormal increase in built up area in cities, loss of green areas, construction of flyovers and under passes has become a great area of concern. Even with a small intensity of rainfall the cities suffer water logging problems in major parts of cities causing complete disruption of normal life and functioning of utility services. The existing system needs a major revamp. Gravity flow of storm water through generally choked and silted surface drains has become a question mark. In this situation, catching the storm water in collection sumps and pumping out the storm water to nearby natural water bodies is the viable answer but this needs planning and design of entire pressure pipeline network. This paper highlights the need and certain salient issues in design of such a system.